Charged groups synergically enhanced elasticity and tunable swelling/shrinking of poly(dialkylaminoethyl methacrylate)/layered silicate nanocomposite cryogels. (12th September 2019) - Tanc, Beril; Orakdogen, Nermin
Abstract: A thorough understanding of inorganic clay-multifunctional polymer interactions of weakly basic polyelectrolyte systems is critical for the improvement of their thermal, pH- and ionic strength-response to serve in biomedical applications. Poly(dialkylaminoethyl methacrylate)-based polymer-clay nanocomposites were synthesized by (cryo)polymerization and conventional crosslinking of weakly basic N, N -dimethylaminoethyl methacrylate (DMAEMA) and anionic 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS) between interlayer spacing of montmorillonite (MMT) layered silicate using the redox-initiator system; APS-TEMED. Formation mechanism as well as thermal stability of nanocomposite cryogels (referred as NC-Cgs/MMT n ) and nanocomposite hydrogels (referred as NC-Hgs/MMT n ) incorporated with various amount of inorganic clay MMT were characterized by uniaxial compression testing, FTIR, XRD and TGA analysis. At low MMT concentrations, equilibrium swelling of NC-Cgs/MMT n and NC-Hgs/MMT n gels in water increased but then, decreased with further increasing the clay concentration. Correspondingly, compressive modulus of the nanocomposite gels exhibited a distinct minimum with respect to MMT concentration. The nanocomposite gels had stronger mechanical strength and larger volume swelling ratio than those for clay-free gels for MMT concentrations ranging from 0.20 to 3.40% (w/v). From the data obtained by compressive measurements, the network chain-length distribution in the nanocomposite networks with respect to MMT concentration was discussed. The results obtained provided more insights into ionic strength-tunable swelling of slightly charged dialkylaminoethyl methacrylate-based polymer-clay nanocomposite gels and supported the development of potential applications combining the swelling and mechanical properties of weakly basic nanocomposite gels as biomedical materials. Graphical abstract: Poly(dialkylaminoethyl methacrylate)/layered silicate nanocomposite cryogels and hydrogels were prepared via cryopolymerization and in situ free-radical crosslinking using various amount of inorganic clay MMT to achieve the desired nanohybrid structure.Image 1 Highlights: Multi-responsive poly(dialkylaminoethyl methacrylate)/layered silicate nanocomposite cryogels and hydrogels were prepared. Cryopolymerization and in situ free-radical crosslinking to achieve the superior characteristics. Integration of inorganic clay particles into weakly cationic polymeric matrix. Effect of (cryo)polymerization temperature, crosslinking degree and clay content on sequential swelling/shrinking behavior. Ionic strength-tunable swelling of slightly charged dialkylaminoethyl methacrylate-based nanocomposite cryogels.